Diseño de un sistema contable administrativo para la caja solidaria “Crediferr” ubicada en el cantón Latacunga provincia de Cotopaxi. - Guanoluisa Valencia, Gissela Nataly (2019)
This project is focused on the design of an Administrative Accounting System for the "CREDIFERR" solidarity fund, whose primary purpose is to facilitate the management of administrative operations and provide a mechanism to obtain clear and precise information on the financial contributions allowing make decisions for the benefit of the institution. In order to carry out the research, the deductive method was used which helps general conclusions to be reached; the analytical one where the probabilities of the project and the field are analyzed to collect real data about the entity by a direct interview to the person in charge of the organization. From the results, it can be issued that the administrative staff does not have knowledge of accounting and administration; therefore, they cannot correctly register the transactions and, consequently, are not able to make right decisions regarding the progress of the solidarity fund, so the Administrative Accounting System will help the entity's managers to improve the preparation of accounting records and the presentation of their respective financial statements. The Administrative Accounting System will facilitate the recording of income and expenditures appropriately; also, this system will help to obtain accurate information regarding accounting and administration, and as a result, actual reports of the economic contributions of each partner may be prepared. This design will be delivered to the solidarity fund "CREDIFERR" so it will be implemented providing solutions in the accounting and administrative area in the future, providing the company with an efficient tool where its economic activities will be recorded weekly and respectively prepare its financial